Quinze anos de ciclos no ensino fundamental: um balanço das pesquisas sobre a sua implantação - Candido Alberto Gomes (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
Presents a review of research conducted in the last 15 years on the implementation of two-year cycles and other alternatives for changing the organization by grade in primary education, presented as innovations adopted against high repetition rates. Although numerous studies focus on restricted experiences, in the form of theses and dissertations, their results point out both to favorable and unfavorable factors in the process of implementation of those innovations. These factors have often been the same along these twenty years. They were particularly related to the failure to convince and engage the actors at school level, as well as to the missing basic conditions to improve teachers work. As a result, public administration proposals were often misinterpreted and distorted at the local level. The reinterpretation of cycles as automatic promotion by teachers and pupils may often lead to increasing access to poor schooling so that social differences are reinforced.